2017
DOI: 10.1111/eci.12795
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte count at onset predicts poststroke outcomes during a 90-day follow-up

Abstract: Smoker had more severe AIS and higher leucocytes and adhesion molecule levels. In the overall cohort, monocyte count was an independent predictor of worse poststroke outcome. Although larger trials are needed, monocyte count might be a cheap prognostic parameter in AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Similar to our study ndings, several studies [16][17][18] have reported that fasting blood sugar is a predictor for future incidence of hypertension and is elevated in hypertensive patients. A higher monocyte count is a surrogate for in ammatory processes and a predictor of future hypertension as reported in one study [19]. Elevated monocyte count was associated with hypertension in our study and this has previously been reported elsewhere [20] in the HIV negative population.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study ndings, several studies [16][17][18] have reported that fasting blood sugar is a predictor for future incidence of hypertension and is elevated in hypertensive patients. A higher monocyte count is a surrogate for in ammatory processes and a predictor of future hypertension as reported in one study [19]. Elevated monocyte count was associated with hypertension in our study and this has previously been reported elsewhere [20] in the HIV negative population.…”
Section: Discussionsupporting
confidence: 90%
“…Following AIS, monocyte levels increase and migrate to the infarct area, contributing to the enlargement of the ischemic lesion (20,21). Bolayır (20) reported that the monocyte count was significantly higher in AIS patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In line, a higher glucocorticoid replacement dose decreases plasma CETP activity in patients, thereby contributing to higher high-density lipoprotein (HDL) cholesterol and an increase in estimated HDL size. X 48 In the overall cohort, monocyte count was an independent predictor of worse poststroke outcome. Although larger trials are needed, monocyte count might be a cheap prognostic parameter in acute ischemic stroke.…”
Section: Bmentioning
confidence: 97%
“…In the 3 years following the publication of the study “Monocyte count at onset predicts poststroke outcomes during a 90‐day follow‐up”, prognostic relevance of monocytes (assessed as decreased lymphocyte‐to‐monocyte ratio) was later confirmed in acute ischaemic stroke. Noteworthy, a relevant prognostic accuracy was also maintained during the first 7 days after acute event .…”
Section: Monocyte Count At Onset Predicts Poststroke Outcomes During mentioning
confidence: 99%